Understanding Facial Muscle Aging: A Surface Electromyography Study. (4th May 2021) - Cotofana, Sebastian; Assemi-Kabir, Shirin; Mardini, Samir; Giunta, Riccardo E; Gotkin, Robert H; Moellhoff, Nicholas; Avelar, Luiz E T; Mercado-Perez, Arnaldo; Lorenc, Z Paul; Frank, Konstantin
Abstract: Background: Facial aging is a multifactorial process that involves all tissues of the face, including skin, muscles, fat, ligaments, and bone. Whereas robust evidence is available for age-related changes of bone and facial fat, the influence of age on facial muscle activity is poorly understood. Objectives: The objective of this study was to investigate the motor unit action potential of facial muscles by utilizing surface-derived, noninvasive electromyography in young and old healthy volunteers. Methods: The study investigated a total of 32 healthy volunteers with a mean [standard deviation] age of 42.6 [19.6] years (range, 21-82 years) and a mean BMI of 23.9 [2.7] kg/m 2 (range, 18.5-29.7 kg/m 2 ) by performing surface-derived, noninvasive facial electromyography. Nine facial muscles were investigated bilaterally, resulting in a total of 1632 measurements of the signal, baseline noise, and signal-to-noise ratio of these muscles. Results: The results of the study revealed that age does not significantly influence the signal ( P = 0.234), the baseline noise ( P = 0.225), or the signal-to-noise ratio ( P = 0.432) of younger individuals (<30 years) vs older individuals (>50 years) in a gender- and BMI-matched statistical model. Exceptions were the zygomaticus major muscle (reduced activity), procerus muscle (increased activity), and corrugator supercilii muscle (increased activity). Conclusions: The results of this facial electromyography study may help to increase the understanding of facial aging. Future studies need to reproduce the results presented herein to further increase our understanding of facial aging.